Perancangan Sistem Pengemasan Barang Otomatis Berbasis PLC Omron - Marsal Nasution; Ahmad Dani; Solly Aryza Lubis (Jurnal Nasional Teknologi Komputer, 2026)
This research aims to design and test Omron's PLC-based automated goods packaging system in the product packaging process. The system combines PLC technology, industrial robots, and sensors to improve efficiency and accuracy in packaging. The test was conducted in two modes, namely manual mode and automatic mode, with a focus on the filling process, bottle cap placement, and bottle cap sealing. The test results showed that in manual mode, the system can pack one bottle in a row, while in automatic mode, the system can pack three bottles efficiently with an efficiency of up to 99.99%. In addition, tests on the actuator and sensor show that all components are in good working order, and the system can detect the position of the bottle as well as control the milk flow with precision. The use of Omron's PLC as a control center provides ease of programming and improves system reliability. Overall, the study shows that Omron's PLC-based automated packaging system is effective in increasing productivity and reducing reliance on manual labor, with the potential to be applied in large-scale packaging industries.